WOMEN AND MUSLIM EDUCATION IN WEST SUMATRA, INDONESIA - Srimulyani, Eka; Firdaus, Firdaus; Sarwan, Sarwan; Hanani, Silfia; Hayati, Syarifatul (Universitas Islam Negeri Ar-Raniry, 2025)
Minangkabau was known for its dominant Islamic education history especially in modern times since the beginning of the twentieth century as a number of so-called madrasah or Islamic educational reforms have been credited to several prominent figures in the region. This region also has a significant history and tradition of matriarchal and matrilineal kinship that relate to women’s position, and their contributions in the public affairs, including in the field of education. Several prominent women from the region have been named as founders of several schools for women, or journalists that campaign for women’s education. This study examines the socio-historical aspects of women and education and the women’s educational movement initiatives from the cases of few female figures such as Rahmah el-Yunusiyyah and others. From a historical perspective and qualitative library research data, this study shows the presence of local female figures in the field of education alongside their male counterparts amidst the kaum muda and kaum tua socio-religious contestation. The socio-local traditions influenced women’s presence and contribution to the public sphere, and those women not only established schools for women but also advocated women’s rights, including their rights for education through journalism and politics.